Small-scale rearing of cuttlefish (Sepia officinalis) for research purposes. Issue 2 (4th March 2017) - Panetta, D.; Solomon, M.; Buresch, K.; Hanlon, R. T.
Abstract: We report a methodology refined over 20 years to culture and maintain a small colony of Sepia officinalis for research year-round. Wild-caught eggs were obtained annually from England and reared in semi-closed natural seawater systems of large volume. Constant temperature (15 °C) and day length (12L/12D) delayed sexual maturation and reproductive behavior. This extended life cycle by roughly 50%, thus providing small research animals for about 18 months from every annual batch of eggs. A novel live food – gammarid crustaceans collected from washed up seagrass– was provided to hatchlings and juveniles. Juveniles were then trained to take thawed shrimp thereafter, thus reducing the expense of live foods. Typical survival to one year was >65%. With these methods, healthy sexually immature cuttlefish were available year-round for behavioral and physiological studies without the confounding influences of hormonally-induced fighting, mating, and egg laying that typically occur within six months.